2010
DOI: 10.1159/000313983
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow-Derived Cells in Neovascular Age-Related Macular Degeneration: Contribution and Potential Application

Abstract: Neovascular age-related macular degeneration, characterized by the formation of choroidal neovascularization (CNV), is a predominant cause of serious loss of vision. The pathogenesis of CNV is complex and still imperfectly understood. Prior studies have shown that bone marrow-derived cells (BMC) play a role in CNV. In this review article, we describe the contribution of BMC to CNV development, and discuss the potential use of BMC in the anticipation and treatment of CNV-associated diseases as well as research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…A crucial pathological aspect of age-related macular degeneration is choroidal neovascularization (CNV), which involves angiogenesis and vasculogenesis and causes severe visual impairments due to the leakage of immature blood vessels and subsequent fibrosis. Studies in recent decades have made considerable progress in exploring the pathogenesis of CNV and the development of new therapeutic approaches [2]. However, the exact mechanism of CNV has not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…A crucial pathological aspect of age-related macular degeneration is choroidal neovascularization (CNV), which involves angiogenesis and vasculogenesis and causes severe visual impairments due to the leakage of immature blood vessels and subsequent fibrosis. Studies in recent decades have made considerable progress in exploring the pathogenesis of CNV and the development of new therapeutic approaches [2]. However, the exact mechanism of CNV has not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies suggest an important role for endothelial progenitor cells (EPCs), hematopoietic stem cells (HSCs) and mesenchymal stem cells (MSCs) in ocular neovascularization [ 4 ]. These stem cells have been shown to differentiate into different several cell types, including vascular components (vascular ECs, vascular smooth muscle cells (VSMCs), and pericytes) and extravascular cells (myofibroblasts, inflammatory cells, retinal pigment epithelial (RPE) cells and glial cells) [ 1 ]. In addition to stem cells, bone marrow (BM)-derived macrophages are key modulators of the severity of ocular neovascularization.…”
Section: Bone Marrow-derived Cells and Ocular Neovascularizationmentioning
confidence: 99%
“…BMCs are affected by several risk factors like aging and are known to regulate the severity of ocular neovascularization formation. Aging BMCs are known to have age-related dysfunction, which may be associated with a more intense response to pro-vascularization factors, an increased number of cells distributed to their corresponding positions and an altered direction of differentiation, thereby enhancing the severity of ocular neovascularization [ 1 ]. In their earlier studies of CNV, Espinosa-Heidmann et al reported the effect of aging on neovascular remodeling [ 73 , 74 ].…”
Section: Risk Factors Affecting Bone Marrow-derived Cells’ Contributimentioning
confidence: 99%
See 1 more Smart Citation
“…Choroidal neovascularization involves both angiogenesis and vasculogenesis (recruitment and in situ differentiation of vascular endothelial cells from circulating bone marrow-derived cells) (Abu El-Asrar et al, 2011;Hou et al, 2011;Zhang et al, 2011). Vascular endothelial growth factor (VEGF) is pivotal in the pathogenesis of choroidal neovascularization, and plays an important role in the development of wet age-related macular degeneration (Bhutto et al, 2006;Huang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%